Pengaruh Static dan Dynamic Stretching terhadap Performa Vertical Jump Pemain Voli Putra Klub Hero Gas Kabupaten Ponorogo - Alfin Nugraha; Hijrin Fithroni; Achmad Widodo; Soni Sulistyarto; Heri Wahyudi (Pusat Riset dan Inovasi Nasional, 2024)
Volleyball is among the most popular and highly desired sport across different communities. Playing volleyball requires technical, physical, mental, and spiritual maturity. Vertical jump is one of the exercises that plays a major role in player performance during the match. Several studies have stated that dynamic stretching is a safer alternative before performing than static stretching. This study aims to see the effects of static stretching and dynamic stretching on the vertical jump performance of volleyball players at the Hero Gas Club, Ponorogo Regency. This study is a Quasi Experiment study with a one group pre-test posttest design. Data analysis used SPSS Version 29 by testing the hypothesis using the Paired Sample t-test. A total of 21 volleyball players at the Hero Gas Club, Ponorogo Regency participated in this study with an average age of 15-18 years (57%), with a height of 156-160 (48%), weight 50-55 (38%), and BMI in the normal category (73%). The average duration of volleyball player training is >2 hours (90%) with a frequency of 3-4 meetings per week (57%). Paired Sample t-test shows the p-value is at (p = 0.000, p < 0.05), so there is a significant influence between static stretching and dynamic stretching on the vertical jump performance of volleyball players at the Hero Gas Club Ponorogo Regency. Choosing the right exercise is very important to support athlete performance and prevent injury during the match.